Smolder - Hamilton, Laurell K. (Anita Blake, vampire hunter, 2023)
"The wedding of the century between vampire hunter Anita Blake and the vampire king of America Jean-Claude is almost here, but an ancient evil arrives in St. Louis and even Jean-Claude's unmatched power isn't enough to save them. Only with the return of a lost love can they hope to combat the monster and save their loved ones and every vampire in the country from being consumed by darkness"--